2005
DOI: 10.1371/journal.pcbi.0040011.eor
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Firing Sensitivity to Morphologic and Active Membrane Parameters

Abstract: Both the excitability of a neuron's membrane, driven by active ion channels, and dendritic morphology contribute to neuronal firing dynamics, but the relative importance and interactions between these features remain poorly understood. Recent modeling studies have shown that different combinations of active conductances can evoke similar firing patterns, but have neglected how morphology might contribute to homeostasis. Parameterizing the morphology of a cylindrical dendrite, we introduce a novel application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 66 publications
(146 reference statements)
1
26
0
Order By: Relevance
“…Over a century ago, Santiago Ramon y Cajal suggested that the great variety of neuronal morphologies reflected different physiological properties of these cells and, consequently, their information-processing functions. This hypothesis has been confirmed by contemporary research (Mainen and Sejnowski, 1996;Nasuto et al, 2001;Sakatani and Hirose, 2003;Weaver and Wearne, 2008).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Over a century ago, Santiago Ramon y Cajal suggested that the great variety of neuronal morphologies reflected different physiological properties of these cells and, consequently, their information-processing functions. This hypothesis has been confirmed by contemporary research (Mainen and Sejnowski, 1996;Nasuto et al, 2001;Sakatani and Hirose, 2003;Weaver and Wearne, 2008).…”
Section: Introductionsupporting
confidence: 61%
“…Computer-assisted microscopy opens the possibility of 3D reconstruction of cell morphologies; but, in most studies, axon or dendrites still are traced manually or semi-manually with a mouse cursor moving over the computer screen (Brown et al, 2005). In the recent years, significant progress has been made in de-velopment of fully automated methods Bjornsson et al, 2008;Kozubek et al, 2004;Pool et al, 2008;Rodriguez et al, 2003Rodriguez et al, , 2006Rodriguez et al, , 2008Roysam et al, 2006;Srinivasan et al, 2007;Vasilkoski and Stepanyants, 2009;Weaver et al, 2004), but several problems still need to be resolved before these methods can widely replace manual methods.…”
Section: Introductionmentioning
confidence: 99%
“…The use of multiple measurements to establish the validity of models is essential because of aforementioned (Section 2.1-2.3) dissociation between different forms of homeostasis and the differential dependence of different measurements on distinct constitutive components (Figures 2 and 3). It is well recognized in the design principle of these techniques that establishing physiological equivalence of only a partial set of measurements does not necessarily ensure that the other measurements which have not been constrained by the validation process are within the physiological ranges (Achard & De Schutter, 2006;Beining, Mongiat, Schwarzacher, Cuntz, & Jedlicka, 2017;Foster et al, 1993;Goldman et al, 2001;Hobbs & Hooper, 2008;Marder, 2011;Marder & Taylor, 2011;Prinz et al, 2003;Prinz et al, 2004;Rathour & Narayanan, 2012a;Rathour & Narayanan, 2014;Srikanth & Narayanan, 2015;Taylor et al, 2009;Tobin, Van Hooser, & Calabrese, 2006;Weaver & Wearne, 2008). If such a stochastic search algorithm fails to yield any valid model that satisfies all the physiological objectives, the interpretation should not be that the specified model configuration is incapable of achieving all objectives.…”
Section: Degeneracy In Neuronal Physiological Propertiesmentioning
confidence: 99%
“…From the standpoint of cellular neurophysiology, two major factors that impact neuronal function are its morphology and the ion channels and receptors that are expressed throughout neuronal membranes. Neuronal morphology has been shown to have strong links with its physiology, spanning a wide variety of functional characteristics, including neuronal excitability, firing patterns, intraneuronal coupling, intrinsic functional maps, somatodendritic subthreshold resonance, back-and forward propagation of electrical potentials and frequency selectivity in firing (Vetter et al 2001;Mainen and Sejnowski 1996;Stiefel and Sejnowski 2007;Ostojic et al 2015;Cannon et al 2010;van Elburg and van Ooyen 2010;van Ooyen et al 2002;Narayanan and Chattarji 2010;Narayanan et al 2005;Dhupia et al 2014;Krichmar et al 2002;Ferrante et al 2013;Beining et al 2017;Weaver and Wearne 2008;Schaefer et al 2003). Neuronal morphology has also been viewed to be a critical cog in solving the wiring optimization problem, which minimizes the cost of space, time, and matter (Cajal 1992;Cuntz et al 2010;Cherniak 1992;Kim et al 2012) towards transmitting input signals most efficiently (Chklovskii 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A second class of studies have assessed pathology-induced or behaviorally relevant dendritic remodeling (atrophy or hypertrophy) in neuronal structures (van Elburg and van Ooyen 2010; van Ooyen et al 2002; Narayanan and Chattarji 2010; Narayanan et al 2005; Dhupia et al 2014). A third class of studies explored the implications for intrinsic morphological heterogeneities within a neuronal subtype(Krichmar et al 2002;Ferrante et al 2013;Beining et al 2017;Weaver and Wearne 2008;Otopalik et al 2017b;Otopalik et al 2019;Otopalik et al 2017a;Schaefer et al 2003).…”
mentioning
confidence: 99%